Penyuluhan Bahaya Bakteri Plak pada Fase Geligi Pergantian di MI Plus Darussaadah Lirboyo Kota Kediri - Ratriana Amiati, Devy; Khafid , Mohammad; Kusumastuti , Endah (Journal of Science and Social Development, 2025)
Abstract. Problem: Dental caries is a disease caused by plaque bacteria. Dental caries often occurs in children aged 6-12 years in the changing teeth phase. Changing teeth are easily damaged by plaque bacteria because at this phase the tooth structure has not matured. Efforts that can be made to avoid dental caries are to provide counseling about the dangers of plaque bacteria in the changing teeth phase. Method: The method used is counseling with an open-ended process-based approach using PowerPoint Presentation (PPT) media and leaflets. The type of data obtained is primary data (pretest and posttest). Results: The results of the counseling obtained an average knowledge before counseling of 54.44% and after counseling of 88.04%.